Twin Mill Sawdust Grinding Machine - Sugtakchan, Konthee; Intawong, Naris; Intawong, Naret (RMUTL Engineering Journal, 2020)
The purpose of this research is to design and develop a multi-purpose wood waste grinder called “Twin Mill Sawdust Grinding Machine”. This machine is able to grind waste mango wood scrap from turning processes, that include a mixing of large and small sized mango wood scrap. The proposed wood crusher machine is designed to use a two-batch sawdust that requires equal motor power. The coarse crusher uses the “Shredding Machine” a crusher for the purpose of digesting large mango wood chips, such as wood bark crumbs, to a smaller size before falling into a fine grinding unit. The fine grinding unit uses the hammer mill mechanism as the grinding set to be finely grinded and filtered by the final grating to allow the sawdust size of 4 mm. The results showed that the machines created in this research were able to grind fine crushed mango wood chips to a size less than 4 mm which was in accordance with the objectives of the project. In addition, the results showed that the efficiency of the grinder was 95%, the production capacity of 340 kg per hour or equal to 2730 kg per day. The economic analysis showed that the cost of crushing wood chips with Twin Mill Sawdust Grinding was 0.163 Baht per kilogram, which translates to a return of investment period of 1 month and 11 days.